2017
DOI: 10.1161/jaha.117.006484
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality and Disability According to Baseline Blood Pressure in Acute Ischemic Stroke Patients Treated by Thrombectomy: A Collaborative Pooled Analysis

Abstract: BackgroundHigh blood pressure (BP) is associated with worse clinical outcomes in the setting of acute ischemic stroke, but the optimal blood pressure target is still a matter of debate. We aimed to study the association between baseline BP and mortality in acute ischemic stroke patients treated by mechanical thrombectomy.Methods and ResultsA total of 1332 acute ischemic stroke patients treated by mechanical thrombectomy were enrolled (from January 2012 to June 2016) in the ETIS (Endovascular Treatment in Ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 46 publications
6
41
0
Order By: Relevance
“…A French study of 1332 patients treated with EVT also reported a J-shaped relationship between SBP and mortality, with a nadir at 157 mm Hg, and a nonlinear relationship between SBP and functional outcome, with a threshold of >177 mm Hg for poor functional outcome. 8 This study also found no relation between low SBP and functional outcome, but SBP <110 mm Hg was associated with an increased risk of death. In various other studies, U-shaped relations of BP with clinical outcomes have been reported for patients with any ischemic stroke, 4 , 7 , 18 , 19 with both extremes of BP associated with poorer outcome, although the reported optimum SBPs varied substantially between studies, ranging from 120 to 130 mm Hg 7 , 19 to 156 to 220 mm Hg in another study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…A French study of 1332 patients treated with EVT also reported a J-shaped relationship between SBP and mortality, with a nadir at 157 mm Hg, and a nonlinear relationship between SBP and functional outcome, with a threshold of >177 mm Hg for poor functional outcome. 8 This study also found no relation between low SBP and functional outcome, but SBP <110 mm Hg was associated with an increased risk of death. In various other studies, U-shaped relations of BP with clinical outcomes have been reported for patients with any ischemic stroke, 4 , 7 , 18 , 19 with both extremes of BP associated with poorer outcome, although the reported optimum SBPs varied substantially between studies, ranging from 120 to 130 mm Hg 7 , 19 to 156 to 220 mm Hg in another study.…”
Section: Discussionmentioning
confidence: 44%
“…Two other studies in patients treated with EVT or with ischemic stroke in general also failed to find an association between SBP and sICH. 4 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of the primary end point, an ordinal logistic regression (shift analysis of the mRS, with score 5 and 6 collapsed into a single group12) was performed, after checking that the assumption of proportional odds was fulfilled 13. We non‐parametrically examined the possibly non‐linear relationship between each BP‐derived variable (PP before MT2; mean PP during MT; coefficient of variability of the PP during MT) and each outcome with restricted cubic splines with 3 knots, corresponding to the 5th, 50th, and 95th percentiles of the BP‐derived variable. Tests for non‐linearity used the likelihood ratio test, comparing the model with only the linear term to the model with the linear and the cubic spline terms 14.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence supports the impact of baseline systolic blood pressure (SBP) on mortality and functional outcome at 3 months in MT treated patients,2, 3 but data on the role of BP variability specifically during the procedure are sparse and limited. The definition of BP variability often differs across studies and the main hemodynamic parameters measured are SBP and mean arterial pressure 4.…”
Section: Introductionmentioning
confidence: 99%